Strategies for implementing activity-based costing in the UK manufacturing industry - Cheung, Wai; Tan, Swee; Tan, Kian; Sutton, Caroline (Cranfield University Press, 2013)
The purpose of this paper is to report the findings with a case study on why activity based costing lacks impact in the UK manufacturing industry. Activity based costing was performed on selected MT range subsystems of an electrical power generator to compare with the current UNN UK’s conven-tional costing system. The results have found that the current costing system works well for the MT products and thus change of costing system is not necessary for these products. The activity based costing system can be partially implemented in UNN UK for areas requiring detailed costing infor-mation such as new renewable products. Based on the result of the case study, this paper also high-lights the strategies need to be considered in order to adopt activity based costing within a typical manufacturing environment.
Keywords: Activity Based Costing; Conventional Costing Method; Strategies of implementing ABC in the manufacturing industry